HUBUNGAN KEJADIAN BAYI BERAT BADAN LAHIR RENDAH DENGAN HIPERBILIRUBINEMIA - Andesty, Dina (JURNAL MEDIA KESEHATAN, 2015)
According to the result of Riskesdas 2010, one of the causes of neonatal mortality inIndonesia was a blood disorder / jaundice / hyperbilirubinemia (6.6%). Hyperbilirubinemia oneof the causes of infant mortality, one of which caused low birth weight. The incidence of hyperbilirubinemiain hospitals dr.M.Yunus Bengkulu in 2013 was 8.9%. The purpose of this studywas to determine the relationship of LBW with hyperbilirubinemia in space perinatalogi dr. M.Yunus Bengkulu 2013. This study used a case-control design. The population in this study all infantsborn in dr. M. Yunus Bengkulu in 2013, amounting to 1,580 babies. Samples were taken fora total of 35 cases in total sampling in the ratio 1: 2 to take control using systematic random samplingtechnique. The study used secondary data from the register book perinatal room. Data analysisusing univariate and bivariate analysis using chi-square analysis. The results showed almosthalf (34.3%) experienced LBW infants and almost half (33.3%) experienced hyperbilirubinemia.Infants with hyperbilirubinemia most (57.1%) had low birth weight. Results of Chi-Square statisticaltest showed a p-value = 0.001 < α of 0.05, meaning that there is a relationship between theincidence of LBW with hyperbilirubinemia. Obtained value OR = 4.5, which means the incidenceof hyperbilirubinemia have a 4.5 times greater risk in LBW infants than non-LBW. It isrecommended for health care workers, especially in the baby room can improve health care inproviding midwifery care to newborns who had low birth weight and increased infant with hyperbilirubinemiahandling.